SYNTHESIS OF STRUCTURALLY COMMUTED SYSTEMS FOR MULTIDIMENSIONAL MOVING OBJECTS CONTROL - Timchenko, V. L.; Kondratenko, U. P. (Radio Electronics, Computer Science, Control, 2011)
The authors apply the method of structurally commuted feedbacks for controlling functions synthesis in closed loop systems of multidimensional moving objects control. The principles of optimal object trajectory construction and determination of controlling functions switching moments in feedback circuits are formulated; the values of control vector are obtained for different types of closed loop systems.